WHAT KIND OF MANAGEMENT DO WE HAVE – THAT’S HOW WE LIVE - Kalyta, Petro (Social Development: Economic and Legal Issues, 2026)
The article examines the essence of modern management in accordance with the international standard ISO 9000 and the features of its implementation in Ukraine. It is shown that in world practice, management is considered as a complex activity that combines strategic management (direct) and operational management (control), forming a new management culture based on the principles of trust, transparency, flexibility and continuous improvement. At the same time, in Ukraine, when adapting international standards, several systemic errors were made: distortion of terminology, substitution of concepts, identification of management with management, formal application of standards and reduction of management to technical regulation. This led to a paradoxical situation: there are hundreds of thousands of certified managers in the country, but the activity of “management” itself is not officially recognized, especially as a separate sphere. The paper outlines the theoretical and methodological, educational and personnel, practical and institutional paradoxes of Ukrainian management, which negatively affect the development of organizations and the state as a whole. In particular, the lack of strategic leadership reduces the effectiveness of management decisions, forms a weak corporate culture and promotes imitation of management. This, in turn, is reflected in macroeconomic indicators: economic recession, staff turnover and the growth of corruption. The author proves that Ukraine is not an underdeveloped country, but rather “poorly managed”, which is consistent with Peter Drucker’s statement: “There are no underdeveloped countries, there are only poorly managed ones”. To overcome these problems, it is proposed to recreate an authentic understanding of management according to ISO 9000, revise educational programs, integrate modern international models (EFQM, Lean, Balanced Scorecard, Kaizen), return management to the public sector, in particular government agencies, and recognize it as an independent strategic area of activity. This will allow to form a modern management culture, increase the effectiveness of organizations, ensure the sustainable development of Ukraine and its competitiveness in the global environment, where the quality of management determines the level of welfare of society and prospects for future development.